Notational Analysis and Physiological and Metabolic Responses of Male Junior Badminton Match Play - Ross Green; Andrew T. West; Mark E. T. Willems (Sports, 2023)
We examined the game characteristics of badminton and the physiological and metabolic responses in highly trained male junior players. Players from a Badminton England accredited Performance Centre (n = 10, age: 14.0 ± 1.2 y, height: 1.69 ± 0.06 m, body mass: 59.1 ± 5.0 kg) completed a 20-m shuttle run test (<semantics><mover accent="true">V˙</mover></semantics>O2max: 64 ± 7 mL·kg−1·min−1) and a simulated ability-matched competitive singles badminton game consisting of two 12-min games with a 2-min break wearing the COSMED K5 metabolic system with notational analysis. In five games, 427 points were contested with a rally time of 5.7 ± 3.7 s, a rest time of 11.2 ± 5.9 s, shots per rally of 5.6 ± 3.6, work density of 0.50 ± 0.21, an effective playing time of 32.3 ± 8.4%, and shots frequency of 1.04 ± 0.29. During badminton play, heart rate was 151 ± 12 b·min−1 (82 ± 10% of maximum heart rate), oxygen uptake was 39.2 ± 3.9 mL·kg−1·min−1 (62 ± 7% of <semantics><mover accent="true">V˙</mover></semantics>O2max), and energy expenditure was 11.2 ± 1.1 kcal·min−1 with a post-game blood lactate of 3.33 ± 0.83 mmol·L−1. Compared to adult badminton play, the physiological responses of junior badminton are lower and may be due to the shorter rally durations. Male junior badminton players should be exposed to training methodologies which include rally durations in excess of what they encounter during match play so as to develop greater consistency. Our observations on game characteristics and physiological responses during junior badminton can be used to inform training practice.